1971
DOI: 10.3181/00379727-137-35538
|View full text |Cite
|
Sign up to set email alerts
|

Maternal--Fetal Endocrine Interrelations: Demonstration of TSH Release from the Fetal Hypophysis in Pregnant Rats Administered Synthetic TRH

Abstract: Intensive physiologic ( 1, 2) and chemical (3, 4) researches during the last decade have recently culminated in the demonstration that the thyrotropin releasing hormone ( T R H ) of the hypothalamus in pigs, cattle, and sheep is a tripeptide, consisting of three amino acids, glu tamic aci d-hi s ti dine-proline (5-7) in that sequence. Bowers and associates (8) have shown further that Sprague Dawley rats (Charles River Breeding Laboratories, Wilmington, Mass.) were maintained in separate cages under controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, maternal administration of TRF induced a rise in fetal TSH concentration, suggesting that TRF receptors are differentiated in the fetal pituitary by day 20 of gestation and that TRF passes the rodent placental barrier (151,152). The 5-day-old infant rat has a lower PRL response to TRF than does the adult rat (153).…”
Section: // Regulation Of Perinatal Prl Secretionmentioning
confidence: 94%
“…However, maternal administration of TRF induced a rise in fetal TSH concentration, suggesting that TRF receptors are differentiated in the fetal pituitary by day 20 of gestation and that TRF passes the rodent placental barrier (151,152). The 5-day-old infant rat has a lower PRL response to TRF than does the adult rat (153).…”
Section: // Regulation Of Perinatal Prl Secretionmentioning
confidence: 94%
“…The administration of TRH is followed by a stimulation of both TSH and prolactin secretion in several species; however, TRH has no effect on prolactin secretion in the rat under normal conditions (4). TRH has been shown to affect the synthesis and release of TSH in the rat during the fetal and neonatal period (5). Although there have been reports on the hypothalamic content of bioactive and immunoreactive TRH (6,7) during the postnatal development, no information is yet available on the evolution pattern of TRH in rat fetuses and on the evolution of TRH in the extrahypo thalamic regions of the brain during the neo natal period.…”
Section: Introductionmentioning
confidence: 98%
“…In the rat, however, D'Angelo, Wall and Bowers (1971) have shown that the fetal adenohypophysis is able to release TSH in response to large amounts (250-500 p g ) of T R H given S.C. to the mother during the perinatal period. Kajihara et al (1972) have found raised colloid droplet formation in the rat fetal thyroid after administration of synthetic T R H i.v.…”
Section: Discussionmentioning
confidence: 99%